2009
DOI: 10.1590/s1415-52732009000200003
|View full text |Cite
|
Sign up to set email alerts
|

Evolução do estado nutricional de crianças submetidas a um programa de suplementação alimentar em município do Estado de São Paulo

Abstract: OBJETIVO: O objetivo deste estudo foi avaliar o impacto do Programa de Incentivo ao Combate às Carências Nutricionais no município de Assis, estado de São Paulo. MÉTODOS: Foram acompanhadas 132 crianças menores de 24 meses, que permaneceram por um ano no Programa de Incentivo ao Combate às Carências Nutricionais. O estado nutricional foi avaliado pelo índice Peso para Idade expresso em escore-Z da mediana da população de referência do Nacional Center Health Statistics no início, aos 2, 6, 9 e 12 meses de acomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
3
0
2
Order By: Relevance
“…Food supplementation programmes with dairy products have been in use for decades, focusing on their contribution to combating child malnutrition and reducing macro-and micronutrient deficiencies. However, few studies have evaluated its effectiveness in positively changing the nutritional status of overweight children [18,[26][27][28][29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food supplementation programmes with dairy products have been in use for decades, focusing on their contribution to combating child malnutrition and reducing macro-and micronutrient deficiencies. However, few studies have evaluated its effectiveness in positively changing the nutritional status of overweight children [18,[26][27][28][29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of food supplementation programmes in Brazil differs in terms of methodology, type of food used for supplementation (cow milk, cow milk supplemented with vegetable oil, or infant formula), intervention duration, and anthropometric indicators. Despite the lack of homogeneity, studies have shown that nutrition programmes improve anthropometric indicators, with children with more significant deficits benefiting the most [19,23,24,27,28,33]. Two exceptions were studies that did not show a response to the nutritional intervention programme; there were failures in maternal adherence and home delivery of milk in one study [31].…”
Section: Discussionmentioning
confidence: 99%
“…This association between the bureaucratic and scientific fields is also evidenced by the fact that among the articles analyzed that revealed the source of resources used in the evaluation, three were carried out with the financial support from the Ministry of Health [14,23,34], and three others received support from international agencies (Food and Agriculture Organization of the United Nations, Inter-American Development Bank, and International Atomic Energy Agency [26,29,30].…”
Section: Type Of Evaluators and Their Affiliation Or Connectionmentioning
confidence: 97%
“…Por sua vez, revisão sistemática de ensaios clínicos randomizados indicou resultado similar no crescimento linear de crianças 9 . Entretanto, existem evidências sobre a influência da condição nutricional e/ou da idade na resposta a uma determinada intervenção nutricional 10 . Estudo de suplementação com vitamina A desenvolvido na Tanzânia, por exemplo, melhorou o crescimento em crianças com anemia 11 .…”
Section: N T R O D U ç ã Ounclassified
“…Estudo de suplementação com vitamina A desenvolvido na Tanzânia, por exemplo, melhorou o crescimento em crianças com anemia 11 . No Brasil, em município do Estado de São Paulo, o benefício de um programa de suplementação alimentar foi maior em crianças com deficits nutricionais e em menores de um ano 10 . Em relação à vitamina A, sabe-se que maior efeito no crescimento é esperado nos casos de estoques funcionais esgotados e/ou quando sua deficiência resulta em um incremento da morbidade 12 , fenô-menos particularmente importantes em crianças.…”
Section: N T R O D U ç ã Ounclassified